Mairiporã: periferização e conflitos ambientais na região metropolitana de São Paulo - Pinto, Celina Maria Rodrigues (2007)
The town of Mairiporã counts on one of the larger environmental historic heritage of the metropolitan region of São Paulo. The whole territory of the municipality is include as Environmental Preservation Area of the Cantareira Range Mountains (State Law nº 10,111 of December 4th , 1998, not yet regulated ) and 80.1% are environmental protected by the State (State Laws Nº 898 of December 18th , 1975 and 1,172 of November 17th, 1976) what is related to its better water quality and quantity that supply the region and with the forest remnants preservation. This work presents the recent urbanization of the Municipality of Mairiporã being part of a historic process of land use changes that involve the whole metropolitan context and its inter-relationship with the critical water supply regional situation.